Etyka – kuracja dla rynków finansowych - KURIATA, Jakub (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
Perhaps one of the most urgent concerns to be addressed today is the ethical dimension of the recent financial crisis. It is by no means an easy task given the characteristics of modern financial sector: excessive risk taking, highly leveraged investment, technological change and globalisation. Moreover, in order to have a pertinent discussion about ethics in finance, we need to establish a common philosophical ground to think about the role of financial markets in the society. There is a large consensus among the mainstream economists that the development of financial sector in a given area has a strong and positive impact on the economic growth. It is very often forgotten during the periods of financial crisis when many people tend to think that financial markets create instability and are “parasitical” upon the real economic activity. To establish a link between ethics and economic theory, I propose the application of some elements of Aristotelian virtue ethics to the ethical judgment about financial markets. According to standard economics, allocation of available resources to their most productive uses and redistribution of risks are two main roles of financial markets. Through this channel financial intermediaries make a positive contribution to the economic growth. Against this backdrop, I argue that we should adopt a teleological approach. Financial markets should be judged by their ability to contribute to the human flourishing (eudaemonia) by performing their functions efficiently. As for Aristotle the definition of eudaemonia is to live according to certain virtues, market participants should also focus on exercising virtuous behaviour. Given that this is a longterm task, I for instance do not reject the advantages of adjusting financial regulations in order to tackle quickly the most urgent issues. In the second part I outline a simple framework to be applied in order to address the fact that financial markets require a multidimensional treatment called diet and consisting of: debate, incentives, education and targeting. In short, debate plus education are to promote virtuous behaviour among market participants and increase the awareness of the public opinion. Changing the structure of incentives within financial institutions is necessary to curb excessive risk taking and reduce the leverage while proper targeting of financial products (according to the client’s needs but also to their understanding and capacity to manage risks) would help allocating properly risk and resources. The paper, in its English version, won the third edition of Ethics in Finance – Robin Cosgrove Prize 2011. The English version was published in Finance and the Common Good/Bien Commun, available from office@obsfin.ch. See: http://www.robincosgroveprize.org/images/pdf/fbc−rcp−2011−j−kuriata.pdf.